Penetapan Kadar Parasetamol dalam Sediaan Tablet Secara Spektrofotometri Inframerah - Jenny J (Program Studi S1 Farmasi, STIKES Senior, Medan, 2021)
Paracetamol is paraaminophenol which is a metabolite of phenacetin and has been used since 1893, paracetamol (acetaminophen) has a working power analgesics, antipyretics, not has anti- inflammatory work power and does not cause irritation and inflammation of the stomach. According to Law Number 36 of 2009 concerning Health in paragraph 1 article 105, it is stated that pharmaceutical preparations in the form of drugs and medicinal raw materials must meet the requirements of Indonesian Pharmacopoeia or other standard books.Thepurpose of this study was to determine paracetamol levels in tablet preparations with a trade name and generic and to determine the suitability of the requirements of Indonesian Pharmacopoeia.Determination of paracetamol levels by Fourier Transform Infra Red (FTIR) spectrophotometry using methanol solvent in the wave number range 4000 - 650 cm-1.The results showed that paracetamol levels in Sanmol®tablets (102,69±9,35)%; Erphamol®tablets(95,42 ± 0,26)%; Farmadol®tablets (99,67±9,87)%; Biogesic®tablets (96,7±2,14)%; Paracetamol tablets (97,98± 0.29)%. From the method validation, the results of the recovery test was 100,18%, RSD was 0.03%, and LOD and LOQ respectively was 0.0973 mg / mL and 0,3244 mg / mL. These results indicate that the method performed shows accurate and precise results. The results of this study concluded that the determination of paracetamol levels could be carried out by Fourier Transform Infra Red (FTIR) spectrophotometry and the levels of paracetamol tablets had met the requirements.